1974
DOI: 10.6028/jres.078a.042
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of -Ca3(PO4)2 in the system Ca(OH)2-H3PO4-H2O at 5, 15, 25, and 37 C

Abstract: Solu bility isoth erms of beta-trica lcium phos ph ate, j3-Ca3(PO.)" prepared by heating mixtures of CaC0 3 an d CaHP O. above 800°C, were dete rmined in th e tern ary system Ca(OH),·H 3PO.-H 20 a t 5, 15,25, and 37°C in the pH range 6.0-7.5 by equilibrati on with dilute H 3PO ., solutions. The results in dicate that j3-Ca3(P0 4), has a negative therm al coefficien t of solu bility. The solubility produ ct , K" was de termin ed as a fun cti on of te mperature by a ge neral ized least-s qu a res procedure; the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(48 citation statements)
references
References 5 publications
(10 reference statements)
2
35
0
Order By: Relevance
“…A matrix effect controls the mobilization of the REE. Dissolution experiments have demonstrated that whitlockite dissolves slightly faster than apatite in acidic solution, the rates of both increase with acidity (Gregory et al 1974). The more ready dissolution of REE from whitlockite of Zagami than from apatite of BE-N suggests that the dissolution rate of the matrix material determines the relative amount of REE dissolution.…”
Section: Factors Determining the Mobilization Of K Ree Th And U Frmentioning
confidence: 99%
“…A matrix effect controls the mobilization of the REE. Dissolution experiments have demonstrated that whitlockite dissolves slightly faster than apatite in acidic solution, the rates of both increase with acidity (Gregory et al 1974). The more ready dissolution of REE from whitlockite of Zagami than from apatite of BE-N suggests that the dissolution rate of the matrix material determines the relative amount of REE dissolution.…”
Section: Factors Determining the Mobilization Of K Ree Th And U Frmentioning
confidence: 99%
“…The pH value of the physiological solution saturated for ¢-TCP was estimated by making a comparison between the calcium concentration in the physiological solution and the solubility curve of ¢-TCP in some aqueous system in previous reports 63) 65) which was simpler than that in the present study. Gregory T.M.…”
Section: )mentioning
confidence: 99%
“…Gregory T.M. et al 63) reported the temperature dependence of the solubility of ¢-TCP in the system Ca(OH) 2 H 3 PO 4 H 2 O at 5, 15, 25, and 37°C. These solubility isotherms indicated that the solubility of ¢-TCP decreased with increasing temperature.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations